2018
DOI: 10.1186/s12918-018-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the regeneration strategies of zebrafish organs: a comprehensive systems biology study on heart, cerebellum, fin, and retina regeneration

Abstract: BackgroundRegeneration is an important biological process for the restoration of organ mass, structure, and function after damage, and involves complex bio-physiological mechanisms including cell differentiation and immune responses. We constructed four regenerative protein-protein interaction (PPI) networks using dynamic models and AIC (Akaike’s Information Criterion), based on time-course microarray data from the regeneration of four zebrafish organs: heart, cerebellum, fin, and retina. We extracted core and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Moreover, direct comparison of the cell types as percentage of total cell count showed all the identified cell types were represented in comparable numbers between untreated and morphine-treated fish (Figure 3C). Plotting the mRNA expression of the individual genes with a defined role in regeneration including aldh1a2, cxcl12a, postnb, gata4, cxcr4b, fn1a, col1a1a , and tgf1b (Bensimon-Brito et al, 2020; Gupta et al, 2013; Itou et al, 2012; Kikuchi et al, 2011; Kim et al, 2010; Liu et al, 2018; Moyse and Richardson, 2020; Sánchez-Iranzo et al, 2018; Wang et al, 2013) did not reveal any significant differences between the untreated and morphine-treated fish (Figure 3D). Quantifying the relative mRNA expression of a subset of these genes further corroborated our scRNAseq data (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, direct comparison of the cell types as percentage of total cell count showed all the identified cell types were represented in comparable numbers between untreated and morphine-treated fish (Figure 3C). Plotting the mRNA expression of the individual genes with a defined role in regeneration including aldh1a2, cxcl12a, postnb, gata4, cxcr4b, fn1a, col1a1a , and tgf1b (Bensimon-Brito et al, 2020; Gupta et al, 2013; Itou et al, 2012; Kikuchi et al, 2011; Kim et al, 2010; Liu et al, 2018; Moyse and Richardson, 2020; Sánchez-Iranzo et al, 2018; Wang et al, 2013) did not reveal any significant differences between the untreated and morphine-treated fish (Figure 3D). Quantifying the relative mRNA expression of a subset of these genes further corroborated our scRNAseq data (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, our detailed comparison of the cellular and molecular responses between control and morphine-treated fish determined major differences neither in the cellular composition nor at the transcriptional level. We have tested not only genes with established roles in the heart regeneration (Bensimon-Brito et al, 2020; Gupta et al, 2013; Itou et al, 2012; Kikuchi et al, 2011; Kim et al, 2010; Liu et al, 2018; Moyse and Richardson, 2020; Sánchez-Iranzo et al, 2018; Wang et al, 2013), but have also probed the proliferative response of CM, which is a hallmark of the zebrafish heart regeneration. We, however, advise caution as the earliest assessed transcriptomes were of hearts isolated at 3dpi, and thus we cannot rule out morphine effects on the early wound healing and on the immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…It has four main advantages relative to its murine counterpart: (1) external development, (2) small size and high fecundity, which support high‐throughput studies, (3) optical clarity, and (4) availability of transgenic reporter lines that allow the visualization of specific cells and organs (Chávez, Aedo, Fierro, Allende, & Egaña, ). Additionally, adult zebrafish exhibit a remarkable regenerative potential in several tissues, including heart, fins, central nervous system, jaw, lateral line, hair cells, pancreas, liver, and kidneys (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The same zebrafish microarray dataset has previously been used to reveal organ-specific regenerative strategies [14] that include the heart-specific pathways also observed in our acute and early-phase response profiles derived from the selected myocardial remodeling genes. In this study, gene regulatory network analysis further revealed that B2M signaling pathways may play an important role in myocardial remodeling during heart regeneration ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Time-course microarray data following wound healing in the zebrafish heart have been published previously (NCBI GEO Dataset: GSE72348) [14]. Briefly, gene expression data for adult zebrafish hearts subjected to ventricular resection were obtained for 0, 0.25, 1, 3, 6, 10, 15, 21, 28 dpa (days post amputation).…”
Section: Gene Expression Microarray Dataset For Zebrafish Heart Regenmentioning
confidence: 99%